Application of industrial robots for producing cores in a foundry: Task time optimization - Al-Dois H.; Jha A.K.; Mishra R.B. (My University, 2025)
This paper describes an approach to develop the kinematic and dynamic models of IRB 6640-180-255, an industrial manipulator from ABB. Models' parameters and constraints that characterize robot motion are extracted frommanuals and tests on the same robot in ABB RobotStudio® environment. RobotStudio® is a software provided by the robot manufacturer and implements a virtual controller identical to the one impeded in the real robots. After building the robot models, the performance of the same robot installed in ElectroSteel Castings Ltd, Kolkata is simulated for a task of producing sand cores in a robotic workcell. The trajectory used for simulation is similar to the one used in the real robot motion. To insure that the robot movement is simulated without violating motion constraints given in themotion command, a task-time optimization is proposed wheremotion constraints are set to limits of joint positions, velocities, accelerations and torques. Finally, the overall task time is optimized by running the robot in maximum velocity and the optimized time is compared to the original task time. Modeling, simulation and task-time optimization are developed in MATLAB®.